God's missional people: reflecting God's love in the midst of suffering and affliction - Frans J. van H. Hancke (Acta Theologica)
The title of this article reflects a deep and personal conviction founded on the belief that a major solution to lessen the suffering of people living in poverty and in the midst of pandemics such as AIDS, lies within the body of Christ. The focus therefore is on God’s people being called to participate in God’s mission in God’s world. Reflecting on those people, his church, in which he is incarnating himself through his Holy Spirit in an extraordinary and empowering way in order for them to reflect his love on the highways and byways of life – to transform the lives and circumstances of people in order for him to receive glory and honour. The title of this article clearly indicates a fundamental characteristic of God’s people – they are being sent to participate in his mission (missio Dei).